(3EfHGg GdCPcjGA aj MjGI GdCfHjGAs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hbY SDGd Cf GdfHi Udi Gddg Ydjg hSde Cfg Mi ai bHQg s
(3BNQgG (B:s
(3hGddg JYGdi CYde HGdUhGH hEdjg GdeQLY hGdeBH GfJgi s
(3Vef eLehY , JQJjHgG (B: 4s
(3JSejI GdQSGdI HcTa GdXfhf ceG hQOJ ai GdYfhGf GdCUdis
(3HjfeG ai gOjI GdYGQajf (B536/1: (3EfHGA GdCPcjGA dMjGI GdCfHjGAs
(3YdjgG hba ddLGeY GdCYXe GdecJHI GdCMeOjI HJhfSs
(3HJGQjN (B1256 (3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdJhMjO hGdedd hGdfMds